Neurofeedback as supplementary training for optimizing athletes` performance: A systematic review with implications for future research - Mirifar, A.; Beckmann, J.; Ehrlenspiel, F. (Neuroscience & Biobehavioral Reviews, 2017)
Self-regulation plays an important role in enhancing human performance. Neurofeedback is a promising noninvasive approach for modifying human brain oscillation and can be utilized in developing skills for self-regulation of brain activity. So far, the effectiveness of neurofeedback has been evaluated with regard to not only its application in clinical populations but also the enhancement of performance in general. However, reviews of the application of neurofeedback training in the sports domain are absent, although this application goes back to 1991, when it was first applied in archery. Sport scientists have shown an increasing interest in this topic in recent years. This article provides an overview of empirical studies examining the effects of neurofeedback in sports and evaluates these studies against cardinal and methodological criteria. Furthermore, it includes guidelines and suggestions for future evaluations of neurofeedback training in sports.